2005
DOI: 10.1007/s00228-005-0896-7
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of erythropoietin in the cerebrospinal fluid after intravenous administration of recombinant human erythropoietin

Abstract: We report that r-HuEPO can cross the human BBB and describe for the first time the PK of EPO in the CSF after IV administration. Our data suggest that the concentration-time profile of EPO in the CSF can be predicted for individual patients if the serum concentration of EPO and the Q(A) are known. This information may be useful in the design of clinical trials to explore the potential therapeutic effects of EPO during CNS injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(63 citation statements)
references
References 23 publications
4
58
0
1
Order By: Relevance
“…In patients given high doses of EPO intravenously, EPO increase in the cerebrospinal fluid was detected as early as 3 h after administration, followed first order kinetics, and depended on permeability of the blood-brain barrier, providing evidence that EPO transport proceeds via a first order transmembrane or non-receptor-mediated mechanism [55]. After single injection of a high level of EPO, cerebrospinal fluid of EPO reached levels up to 40 mIU/ml with a halflife similar to serum (26 h to 36 h).…”
Section: Intravenous Epo Administration In Patients and Non-human Primentioning
confidence: 96%
“…In patients given high doses of EPO intravenously, EPO increase in the cerebrospinal fluid was detected as early as 3 h after administration, followed first order kinetics, and depended on permeability of the blood-brain barrier, providing evidence that EPO transport proceeds via a first order transmembrane or non-receptor-mediated mechanism [55]. After single injection of a high level of EPO, cerebrospinal fluid of EPO reached levels up to 40 mIU/ml with a halflife similar to serum (26 h to 36 h).…”
Section: Intravenous Epo Administration In Patients and Non-human Primentioning
confidence: 96%
“…The molecular basis for this observation has not been established, but might be related to increased translation or stabilization of frataxin protein. In earlier studies, rhu-EPO was shown to cross the blood-brain barrier in a human pharmacokinetics study (Xenocostas et al, 2005) and in an animal model for brain injury (Brines et al, 2000). Clinical trials with rhuEPO are currently in progress.…”
Section: Discovery Of Molecules That Increase Frataxin Mrna or Proteinmentioning
confidence: 99%
“…In contrast, EPO administered 30 min before water loading was not effective (data not shown). This is likely due to the substantial delay of several hours in the transport of peripherally-administered EPO into the brain (5,16).…”
Section: Epo Protects Against Neurological Symptoms Caused By Brain Ementioning
confidence: 99%